Rural versus metropolitan comparison of processes of care in the community‐based management of TIA and minor stroke in Australia (an analysis from the INSIST study). (16th November 2022) - Gangadharan, Shyam; Tomari, Shinya; Levi, Christopher R.; Weaver, Natasha; Holliday, Elizabeth; Bajorek, Beata; Lasserson, Daniel; Valderas, Jose M.; Dewey, Helen M.; Barber, Peter Alan; Spratt, Neil J.; Cadilhac, Dominique A.; et al.
Abstract: Objectives: To compare processes of care and clinical outcomes of community‐based management of TIAs and minor strokes (TIAMS) between rural and metropolitan Australia. Design: Inception cohort study between 2012 and 2016 with 12‐month follow‐up after index event (sub‐study of INSIST). Setting: Hunter and Manning valley regions of New South Wales, within the referral territory of the John Hunter Hospital Acute Neurovascular Clinic (JHHANC). Participants: Consecutive patients of 16 participating general practices, presenting with possible TIAMS to either primary or secondary care. Main Outcome Measures: Processes of care (referrals, key management processes, time‐based metrics) and clinical outcomes. Results: Of 613 participants with possible TIAMS who completed the baseline interview, 298 were adjudicated as having TIAMS (119 from rural, 179 from metropolitan). Mean age was 72.3 years (SD, 10.7) and 127 (43%) were women. Rural participants were more likely to be managed solely by a general practitioner (GP) than metropolitan participants (34% v 20%) and less likely to be referred to a JHHANC specialist (13% v 38%) or have brain magnetic resonance imaging (MRI) [24% v 51%]. Those rural participants who were referred, also waited longer (both p  < 0.001). Recurrent stroke, myocardial infarction and death at 12 months were not significantly different between rural and metropolitan participants. Conclusions: Although TIAMS prognosis in rural settings where solely GP care is common is very good, the processes of care in such areas are inferior to metropolitan. This suggests there is further scope to support rural GPs to optimise care of TIAMS patients.